PENGEMBANGAN MODEL SUPERVISI AKADEMIK MATA PELAJARAN IPA (BIOLOGI) DI SMU : Efektivitas Model Inovasi Supervisi Akademik Mata Pelajaran Biologi Dalam Upaya Meningkatkan Kinerja Guru IPA/ Biologi di SMU - Herawan, Dedi (2010)
The qualitative completed by quantitative research (pretest-posttest) is intended to study the present academic supervision model, and to evaluate effectiveness of the model developed based on eight indicators. Population of this research are high school teacher's of biology, principals, and science cluster supervisor in Tasikmalaya. Research instrument of present academic supervision execution, and its development namely: (1) observation guide, (2) interview guide, (3) teaching document guide, (4) questionnaire on biology teaching service based on the minimum service standard. Data analysis for the present academic supervision with the content analysis through unity, category and description process. Data analysis for development of academic supervision is conducted quantitatively with t-test and anova (uses SPSS version 10). The present result of academic supervision (2001-2002) indicates that supervisors knows and understands his role, which is reflected through class-visit execution completed with the feedback to improve teaching quality. But its implementation is still focused on teaching document, means: (1) teacher's supervised obeys the supervisor's instruments, (2) learning resources have not been optimalized yet, (3) content oriented rather than competence oriented. Based on the research above, the model of academic supervision instrument is developed based on standard of minimum service in learning biology, which consists of: (1) essential teaching material, (2) teaching and learning condition, (3) output quality, (4) accuracy and efficiency of teaching and learning system, (5) teaching and learning approach, (6) teaching material mastery, (7) basic teaching skill, and (8) evaluation process. The eight components are used as comparison to the on-going model through giving pretest and posttest/performance test. The result is that both teachers and supervisors tend to adopt the developed model rather the on-going model they applied. The result of the posttest, nevertheless, that there is significant tendency in teachers and supervisors performance becomes lower in implementing the developed model. The next step is conducting the research towards the arguments offered by both teachers and supervisors which become innovation factors function as catalyst for continuous implementation of developed academic supervision model. The innovation indicators are: (1) improvement of teacher's knowledge toward theory of biology, (2) management of teaching and learning activity in social hierarchy, (3) conducting practice and assigning tasks when classroom teaching and learning time for presenting theoretical knowledge is not adequate. The innovation indicators used to formulate and improve the following standard of teaching-learning achievement, the standard are: (1) teaching, (2) teacher's profession development, (3) evaluation, (4) content of biology. The present supervision model is still ineffective in improving the quality of teaching biology. Development model with the innovation factor will improving the commitment towards performance of teacher and supervisor. It is suggested that supervisor improve his competence on teaching management quality and teaching material through local training and education, teachers should conduct self assessment. Supervision program should direct towards the improvement and achievement of minimum service standard, and quality assurance. It is necessary to conduct continuous research on academic supervision model caring the resistance and characteristic of teachers, principals, supervisor and also social structure and local cultivate.